2008
DOI: 10.1002/bit.22011
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and anti‐tumor efficiency evaluation of doxorubicin‐loaded bacterial magnetosomes: Magnetic nanoparticles as drug carriers isolated from Magnetospirillum gryphiswaldense

Abstract: Bacterial magnetosomes (BMs) are commonly used as vehicles for certain enzymes, nucleic acids and antibodies, although they have never been considered drug carriers. To evaluate the clinical potential of BMs extracted from Magnetospirillum gryphiswaldense in cancer therapy, doxorubicin (DOX) was loaded onto the purified BMs at a ratio of 0.87 +/- 0.08 mg/mg using glutaraldehyde. The DOX-coupled BMs (DBMs) and BMs exhibited uniform sizes and morphology evaluated by TEM. The diameters of DBMs and BMs obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 41 publications
(62 reference statements)
4
101
2
1
Order By: Relevance
“…Here, the inhibition rate of BMs was 48%, which is close to the findings of a previous study. 15 As Figure 11A shows, the control group, when incubated for 48 hours, showed a rapid proliferation, with characteristic round, translucent particles, moderate density, and good dispersion. Ara-C and ABMs-P both suppressed cell growth ( Figure 11B-D).…”
Section: Influence Of Abms-p On Hl-60 Cells In Response To Drug Concementioning
confidence: 89%
See 1 more Smart Citation
“…Here, the inhibition rate of BMs was 48%, which is close to the findings of a previous study. 15 As Figure 11A shows, the control group, when incubated for 48 hours, showed a rapid proliferation, with characteristic round, translucent particles, moderate density, and good dispersion. Ara-C and ABMs-P both suppressed cell growth ( Figure 11B-D).…”
Section: Influence Of Abms-p On Hl-60 Cells In Response To Drug Concementioning
confidence: 89%
“…As the nanocarrier of a targeting drug, BMs have many advantages in medical applications, including narrow size Because BMs possess a natural membrane consisting of lipids and abundant amino groups, a previous study has found that BMs can be used as drug carriers after introducing coupling reagents, such as glutaraldehyde. 15 Moreover, in order to improve the drug-loading ratio, a novel cross-linking method has also been investigated, through the surface modification of BMs by poly-l-glutamic acid (PLGA). 16 Because of the potential toxicity of glutaraldehyde, we have successfully prepared a BM drug delivery system that relies on genipin (GP), instead of glutaraldehyde, for crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…Such nanoparticles find diverse applications, especially in biomedical field, such as in magnetic resonance imaging [106], cell tracking [107], drug delivery [108,109], and gene delivery [110].…”
Section: Microbial Cell Factories: Manufacturing Functional Metabolitesmentioning
confidence: 99%
“…It has been shown that BMs coupled with doxorubicin (DOX) display a potential antitumor property. [8][9][10][11][12][13] However, bacterial cultivation is still a problem. The efficiency of BMs used in the magnetic hyperthermia treatment of tumors needs more experimental data to be understood.…”
mentioning
confidence: 99%